The design and evaluation of an ozone contactor-reactor for color and organic matter removal in distellery wastewater - Mercader, Shalom Brian R. (2010)
The study focused on the development of ozone contactor-reactor design for the purpose of eleiminating melanoidin, which is a major by-product of distillation industries and identified as the major colorant in sugarcane molasses wastewater.
About 6-15 liters of spent wash with approximately 2% melanoidin is generated per liter of alcohol produced. Beneficial effect such as antioxidant, antiallergenic and antimicrobial properties have been documented as reported in foodstuffs having melanoidin such as coffee and tea. Harmful effect such as mutagenic, carcinogenic and cytoxic effects have also been reported. Melanoidin present in waste waters is highly resistant to microbial attack making it a persistent pollutant.
Ozonation is an advanced oxidation process currently used in the disinfection of drinking water and more recently in the treatment of wastewaters. The commercial viability of ozonation as a waste water treatment process lies in its superior oxidation potential which allows it to attack inorganic matter such as dyes, pesticides and other industrial pollutants, as well as pathogens which are resistant to chlorine. Despite high operating costs, ozonation has been implemented where conventional treatment processes perform poorly such as non-biodegradable pollutants, wastewaters with toxins, and in the disinfection of drinking water infected with chlorine-resistant cryptosporidium and giardia. Reducing the operating cost of the ozonation process will provide alternative solutions to both industrial pollution and drinking water scarcity.
The resulting process was a combination of ozonation and foam-fractionation process. Configuration-wise, the design resembled a hybrid of the Turbine Mixer Contactor and Ozone Bubble Contactor configurations described by the USEPA Alternative Disinfectants and Oxidants Guidance Manual. Distillery slops from Absolute Chemicals in Nasugbu Batangas an ethanol producer, was used to evaluate the designed ozonator diluted 20, 70 and 100 times. Analysis of COD and color were condi=ucted on the contactor effluent using the Closed Reflux Colorimetric Method and absorbance at the peak wavelength. pH was measured using a caliberated pen-type pH meter. Ozone gas was supplied by an air-fed, air-cooloed ozone generator producing one gram ozone per hour.
Bubble size was approximated by photography, and to compare the performance of the designed system, a batch test was conducted to compare with batch test data from similar runs using an ordinary air stone gas diffuser. In batch trials, the designed ozone contactor-reactor performed 102% beyyer in terms of COD removal and 13.25% better in terms of color removal. Color reduction increased with increasing dilution and flowrate. In continuous runs, a color reduction of 40.875 color units per liter-mg-ozone was achieved at seventy times wastewater dilution, 10 minutes hydraulic residence time and 1 gram per hour ozone introduction. In 10 minutes HRT, COD was reduced by 415.83 mg o2 while color was reduced by 272.5 color units. The froth collected had 44 times the COD level of the influent, had a grainy texture and noticeably different color. Higher percentage removal is expected if the retention time in the continuous reactor is extended, the ozone gas purity is increased and the overall mass introduction is increased. Color reduction relying on ozonation is recommended for use after a secondary clarifier as a polishing stage with a higher rate of ozone introduction and purity.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Ozone contactor reactor